The Influence of Off-Farm Employment On Rice Farming In The Kabupaten (District) Of Banjar South Kalimantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The research is aimed to know the influence of off-farm employment to rice production and total factor productivity, intensification quality of rice farming, the use of labor on rice farming. The research is also aimed to know the contribution of off-farm income to farmers total income and to know the factors influencing off-farm employment. The samples are 80 farmers, that can be divided into two strata. Forty farmers are merely working on rice farming as strata I and 40 farmers as strata H are that either working on rice farming and off-farm employment. Off-farm employment will have some negative influences to rice production, it means that the greater is the off-farm employment the lower is rice production. Off-farm employment does not influence the use of family and hired labor in rice farming. Income contribution of off farm income is fifty percentage of total family income. Rice farming income of farmers are merely working on rice farming on rice farming and off-farm employment, but the total income of farmers is opposite. The members of family working in rice farming have some positive influences to off-farm employment, that productivity of off-farm employment has a negative influence to off-farm employment.